Association of SNP g.643G>A of MYF5 gene polymorphism with body weight and body measurements in Bali cattle - Saputra, E. A.; Ulum, M. F.; Jakaria, J. (Diponegoro University, 2020)
This study aimedto identify the SNP g.643G>Aof MYF5 genethen associate it with body weight and body size measurements in Bali cattle. Blood samples were collectedfrom 80 bali cattle at BPTU-HPT Denpasar Bali. Data on phenotypic properties observed included; birth weight, live weight, average daily gain, body length, chest depth, withers height, hip height, and heart girth. Polymorphismof the MYF5 gene was identifiedusing the PCR-RFLP method. Association of MYF5 genotypes with body weight and body size measurementswas performed using General Linear Model by SAS 9.4 program. MYF5│MspI gene was polymorphic with three genotypes: AA, AG, and GG. Genotype frequency of AA, AG and GG were 0.04 (3), 0.30 (24), and 0.65 (53), respectively. Allele frequencies were 0.19 and 0.81 for A and G alleles, respectively. Gene frequency analysis showed that Bali cattle at BPTU-HPT Denpasar was in Hardy-Weinberg Equilibrium. Association of MYF5│MspI gene with body weight and body measurement were not significantly different. SNP g.643G>A could not be used as a genetic marker for the body weight and body size measurements in Bali cattle.